The Impact of workplace bullying on university teachers self- efficacy: Mediating role of the university environment - Bukhari, Syeda Tehmina Naz; Akhter, Nasreen; Fida, Farah (The journal of contemporary issues in business and government, 2022)
Academics are not immune to workplace bullying. Several studies show that academic institutions have a higher rate of bullying than other organizations the overall nature of bullying's effects showsthat the victim, the people surrounding him or her, and the organization all suffer or are unable to function as effectively as previously. (Keashly and Jagatic 2011).The study investigated the impact of workplace bullying (WPB) on the university environment (UE) and the mediating function of the UE with the relationship between WPB and teacher self-efficacy (TSE). Survey data were obtained from 665 University faculty members from Pakistan.The proposed relationships were evaluated using SMART-PLS structural equation modeling.Significant impact of WPB on UE and TSE was found in this study.In addition, the study found that UE has a considerable impact on TSE, while WPB has an indirect impact on TSE through UE.The study is significant since there is a dearth of workplace bullying research in Pakistani universities. A very little research has been done on the effect of workplace bullying as a key indicator of university environment and research on the effect of university environment on self-efficacy of the teachers.This study is one of the first attempts to evaluate the relationship between WPB, UE, and TSE.This study has essential practical consequences for practitioners in higher education since it contains important information about the relationship between the university environment, teacher self-efficacy, and workplace bullying incidents.